Experimental study of the static and dynamic behavior of a novel heat driven electronic controlled expansion valve. (5th March 2020) - García del Valle, J.; Quinatoa Quinatoa, K.J.; Castro Ruiz, F.
Highlights: Experimental investigation of a novel heat driven expansion valve. New control loop based on average output and measured signal feedback. Precise control of the superheating for the steady and transient states. A mathematical model is employed to derive control loop parameters. Abstract: In this work, a heat driven thermostatic valve is described and tested. The proposed valve is based on a thermostatic expansion valve, where a heating element is wounded to its sensing bulb. By means of controlling the power supplied to the heating device, the degree of superheating at the outlet of the evaporator can be easily controlled. Such arrangement has not been proposed in the open literature. The proposed setup has been tested in an experimental rig operating with R134a. The system behavior for both steady state and transient loads has been compared for the original thermostatic expansion valve setup and the modified one. A mathematical model of the installation has been developed to perform parametric analyses regarding the type of control loop to be used for the heating element. It has been found that the proposed arrangement is able to control the superheating successfully, with a maximum deviation from the set point of 0.02 °C and 0.17 °C for the steady and transient state respectively. Furthermore, the superheating oscillations are reduced in relation with the original valve configuration, thus preventing hunting in the evaporator at low loads.